Er wordt nog steeds gediskrimineerd : wat doet de psychologie daaraan - Boonstra, Jaap; Bothof, Peter; Tortike, Har (Leiden : Psychologisch Instituut, 1979)
Fonds Suzan Daniel (FSD)
Nederlands
Brochure